The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1590/0102-33062020abb0269
|View full text |Cite
|
Sign up to set email alerts
|

Influence of abiotic factors on phytoplankton diversity and distribution in an atoll environment

Abstract: Taxonomic investigations of phytoplankton community structure are very important for understanding the dynamics of these organisms in places like reefs, which present broad hydro-biological variation. This study aimed to determine and investigate phytoplankton community composition and biomass in natural pools of Atol das Rocas (3°51' S; 33°49' W), and to evaluate the possible influences of abiotic variables throughout different seasons. The oceanographic parameters used to assess the phytoplankton community a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…This suggests that this heterotrophic dinoflagellate prefers waters with lower nutrient concentrations. The phytoplankton diversity and distribution in the atoll were primarily associated with nutrients concentration (Jales et al, 2022). Under favorable nutrient conditions, including the presence of dissolved inorganic nitrogen, dissolved inorganic phosphorus and a suitable optimal temperature, phytoplankton exhibited high growth rates throughout the upwelling process from Shanwei to Shantou-Dongshan (Hu et al, 2015).…”
Section: The Response Of Phytoplankton Abundance Variation To Chemica...mentioning
confidence: 99%
See 3 more Smart Citations
“…This suggests that this heterotrophic dinoflagellate prefers waters with lower nutrient concentrations. The phytoplankton diversity and distribution in the atoll were primarily associated with nutrients concentration (Jales et al, 2022). Under favorable nutrient conditions, including the presence of dissolved inorganic nitrogen, dissolved inorganic phosphorus and a suitable optimal temperature, phytoplankton exhibited high growth rates throughout the upwelling process from Shanwei to Shantou-Dongshan (Hu et al, 2015).…”
Section: The Response Of Phytoplankton Abundance Variation To Chemica...mentioning
confidence: 99%
“…Najmi et al (2022) have verified that the presence of a substantial amount of phytoplankton is crucial for the survival of zooplankton, and together, they play a vital role in maintaining the sustainability of coral reefs. In coral atolls like the central South China Sea, the south of the Atlantic Ocean, and the Gulf of Aqaba (Red Sea), diatoms and dinoflagellates emerge as the predominant groups (Ke et al, 2018;Jales et al, 2022;Şahin et al, 2022). These findings align with our own research, highlighting the interconnectedness of phytoplankton, zooplankton, and coral reefs.…”
Section: The Response Of the Phytoplankton Community To Biotic Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aside from physical and biological environmental factors, Wei et al (2022) found that variations strongly influence the abundance and composition of phytoplankton in predatory factors. As Jales et al (2021) stated, biological and physical factors such as environmental changes, nutrients, and the presence of herbivorous zooplankton affect the species composition and diversity of phytoplankton in the ecosystem. Furthermore, the zooplankton community had a low diversity index (H') of 0.81±0.16 at Tuban salt ponds (TSS), a moderate diversity index (H') of a level 1.64±0.04 at Brebes salt ponds (BSR), a depressed evenness index (E) that ranged from 0.18-0.22; and a low dominance index (C) that ranged from 0.03-0.30 at the three salt pond locations.…”
Section: Distribution Of Plankton Communitiesmentioning
confidence: 99%